A study of preschool teachers' intrinsic and extrinsie job satisfaction and their turnover intention in Klang Valley - Tan, Pei En (2024)
This paper investigates the relationship between intrinsic and extrinsic job satisfaction among preschool teachers in the Klang Valley. It aims to explore various aspects of job satisfaction, specifically intrinsic factors such as autonomy, professional development, and social standing, as well as extrinsic factors such as working conditions, pay and workload, organizational policies, and colleagues, in relation to turnover intention. The study addresses the critical need to foster high job satisfaction among preschool educators to mitigate turnover intentions, considering the significant impact of preschool teachers on children's overall development. Despite existing research on job satisfaction among teachers in other educational levels, there is still a noticeable gap concerning these dynamics within early childhood education. To address this gap, the study focuses on determining the relationship between job satisfaction and turnover intention among preschool teachers in Klang Valley, Malaysia. With a quantitative research approach incorporating a correlation design the study used the MSQ Short Form and TIS-6. Convenience sampling was employed to gather the data from 70 preschool teachers in Klang Valley teaching children aged between 4 and 6 years old. The findings suggest a significant relationship between intrinsic and extrinsic factors and teachers' turnover intention. Implications of the study underscore the importance of addressing both intrinsic and extrinsic factors to enhance job satisfaction and reduce turnover intention among preschool teachers. Furthermore, the findings have significant implications for nongovernmental organizations (NGOs) and early childhood education (ECE) professionals, emphasizing the importance of intrinsic motivation in fostering high job satisfaction and low turnover intention among preschool teachers. Recommendations include extending the data collection timeframe, increasing the number of questionnaires distributed, or switching to paper survey methods, employing mixed methods, and enlarging the sample size or utilizing probability sampling to address limitations.